(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes the role of international experiences in the development of inclusive education for children of preschool and primary school age and the possibilities of their implementation in the conditions of Uzbekistan. The article also studies the basic principles, methods and infrastructure of inclusive education using the examples of successful experiences of countries such as Finland, the USA and Japan. The reforms being carried out in this direction in Uzbekistan are analyzed based on existing problems, statistics and research results. At the end of the article, proposals are made for solving existing problems and the need to form a national model of inclusive education in Uzbekistan is justified.